Do socio-cultural practices by elderly women influence obstetric complications? A study in Limpopo province - Langanani C. Makhado; Ndidzulafhi S. Raliphaswa; Mary Maluleke; Mutshinyalo L. Netshikweta (Curationis)
Background: Worldwide, women continue to die from obstetric-related complications, despite the global progress made to reduce maternal mortality. Elderly women play a key role in using their own socio-cultural practices during pregnancy and childbirth.